2009
DOI: 10.1007/s00374-009-0403-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions from an apple orchard soil in the semiarid Loess Plateau of China

Abstract: . Annual emission factor of the apple orchard from the applied fertilizer (uncorrected for background emission) was 0.658%. This value was nearly a half (53%) of the default value provided by the Intergovernmental Panel on Climate Change for the application of synthetic fertilizers to cropland (1.25%). Therefore, the amount of N 2 O emissions from the semiarid apple orchard soil could be largely overestimated if no regional-specific factor is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
5
16
2
Order By: Relevance
“…Considerable variability in N 2 O emissions was found between sites, within orchards and treatment replicates and between seasons, reflected in the high standard errors of the means (Table 3). The magnitude of the maximum daily values more closely followed N 2 O emissions from Australian rainforests than perennial tree crops receiving N fertiliser and irrigation (Pang et al 2009;Rowlings et al 2013;Xia et al 2014;Ge et al 2015). Pang et al (2009) reported an average of 9.35 g N 2 O-N ha -1 day -1 and Ge et al (2015) reported an average of a much higher 36 g N 2 O-N ha -1 day -1 for apple orchards in China -both were orders of magnitude above the average reported here.…”
Section: Temporal and Spatial Variability Of N 2 O Emissionssupporting
confidence: 60%
See 3 more Smart Citations
“…Considerable variability in N 2 O emissions was found between sites, within orchards and treatment replicates and between seasons, reflected in the high standard errors of the means (Table 3). The magnitude of the maximum daily values more closely followed N 2 O emissions from Australian rainforests than perennial tree crops receiving N fertiliser and irrigation (Pang et al 2009;Rowlings et al 2013;Xia et al 2014;Ge et al 2015). Pang et al (2009) reported an average of 9.35 g N 2 O-N ha -1 day -1 and Ge et al (2015) reported an average of a much higher 36 g N 2 O-N ha -1 day -1 for apple orchards in China -both were orders of magnitude above the average reported here.…”
Section: Temporal and Spatial Variability Of N 2 O Emissionssupporting
confidence: 60%
“…The magnitude of the maximum daily values more closely followed N 2 O emissions from Australian rainforests than perennial tree crops receiving N fertiliser and irrigation (Pang et al 2009;Rowlings et al 2013;Xia et al 2014;Ge et al 2015). Pang et al (2009) reported an average of 9.35 g N 2 O-N ha -1 day -1 and Ge et al (2015) reported an average of a much higher 36 g N 2 O-N ha -1 day -1 for apple orchards in China -both were orders of magnitude above the average reported here. In another study of horticulture crops from sub-tropical soils, Huang et al (2012) reported average daily N 2 O emissions of 4.6, 5.9 and 3.3 g N 2 O-N ha -1 day -1 for mango, custard apple and pineapple respectively.…”
Section: Temporal and Spatial Variability Of N 2 O Emissionssupporting
confidence: 60%
See 2 more Smart Citations
“…All bottles were incubated at 25 C in the dark for 24 h. Gas samples (1 mL) were withdrawn from bottles by glass precision gas syringes and were injected into N 2 -filled (1 atm) 29.0 mL vials capped with butyl rubber septa. These diluted gas samples were then analyzed for N 2 O by a gas chromatograph (SP3410, Beijing Analytical Instrument Factory) connected to an ECD detector as described previously by Pang et al (2009), and the amount of N 2 O in the headspace and PDA were calculated as indicated by Schinner et al (1996).…”
Section: Potential Denitrification Activitymentioning
confidence: 99%